AKIBAT HUKUM PENGANGKATAN ANAK SECARA LANGSUNG DALAM MASYARAKAT TIONGHOA - Theo Oematan (Fakultas Hukum Universitas Kristen Indonesia, 2021)
Children are the most important part of the family, there are many families whose marriages are not blessed with a child. This is the background of adoption in society, especially for families who do not have a child. However, direct adoption of children still occurs, without following the procedures in existing laws and regulations, namely through court rulings. This research is an empirical study using the problem approach method used in this study is a sociological juridical approach. The problem in this writing is the provisions for adoption and the position and inheritance rights of adopted children according to Chinese customary law and jurisprudence in Indonesia and the legal consequences for adoptive parents who falsify the birth certificate documents of their adopted children. The result of this research is that adoption of children based on Chinese customs is carried out simply by means of direct adoption, but due to the direct adoption law, which is not based on the applicable law, the party who adopts the child can be sentenced for violating Article 278 of the Criminal Code. Keywords: direct adoption, Chinese adopted children, adoption in Chinese society